A theoretical study of the electronic structure and bonding of the monoclinic phase of Mg2 NiH4 - Jasen, Paula Verónica (2007)
The electronic properties of the Mg2 NiH4 monoclinic phase are calculated using a density functional approach calculation. The crystalline parameters and interatomic distances calculated are close to the experimental values within a 3% error. We also evaluate the density of states (DOS) and character of the chemical bonding for the hydrogen's located in their equilibrium positions. While the Ni-Mg interaction is dominant in the pure alloy, in the hydride the hydrogen atoms present a bonding much more developed with Ni than with Mg. The principal bonding interaction is Ni sp-H s. Moreover, a small bonding between Ni deg and H 1s is observed. Up the Fermi level, the Ni-H interaction is slightly antibonding. The Mg-Ni bonding interactions are weaker in the hydride phase when compared with the pure Mg2 Ni alloy. The present study is potentially useful because the alloys Mg-Ni are good materials for hydrogen storage. © 2007 International Association for Hydrogen Energy.